Faculties’ Satisfaction With Distance Education During COVID-19 Outbreak in Jordan - Jarab, Fadi; Al-Qerem, Walid; Jarab, Anan S.; Banyhani, Meriam (Frontiers in Education, 2022)
Although online teaching has been implemented worldwide, specifically in higher education, resistance to technology use exists, as faculty members may lack technology familiarity and may require both guidance and training. The present study evaluated faculty members’ satisfaction towards distance teaching as imposed during the COVID-19 pandemic. An online survey which evaluated socio-demographics and faculties ‘satisfaction toward distance education was validated and completed by 286 faculties from different faculty-fields of education across all Universities in Jordan. Factor analysis was conducted to validate the questionnaire and univariable analysis was conducted to evaluate demographic variables association with satisfaction degree. The confirmatory factor analysis indicated that the most suitable structure for the study data was a 3-factor model constructed from 21 items. The three factors were students-related factor, institution-related factor and technology-related factor. The scores for the three factors were 2.66, 2.00 and 3.33 out of 5 respectively. Faculties who received training for online teaching and those who have attended courses as a trainee were more satisfied with distance education. In conclusion, the faculties’ low satisfaction level reported in the present study shows margin for distance education improvement by conducting intensive training courses for online teaching with the aim of improving faculties’ satisfaction levels towards a web-based teaching environment and hence improving education outcomes.